Roles of distinct nuclear receptors in diabetic cardiomyopathy - Zheng, Yangyang; Xu, Yongji; Ji, Li; San, Wenqing; Shen, Danning; Zhou, Qianyou; Meng, Guoliang; Shi, Jiahai; Chen, Yun (Frontiers in Pharmacology, 2024)
Diabetes mellitus (DM) induces a pathophysiological disorder known as diabetic cardiomyopathy (DCM) which may eventually cause heart failure (HF). It is manifested with systolic and diastolic contractile dysfunction along with alterations in unique cardiomyocyte proteins and diminished cardiomyocyte contraction. Multiple mechanisms contribute to the pathology of DCM, mainly including abnormal insulin metabolism, hyperglycemia, and glycotoxicity, cardiac lipotoxicity, endoplasmic reticulum (ER) stress, oxidative stress, mitochondrial dysfunction, calcium treatment damage, programmed myocardial cell death, improper Renin-angiotensin-aldosterone System (RAAS) activation, maladaptive immune modulation, coronary artery endothelial dysfunction, and exocrine dysfunction, etc. There is an urgent need to investigate the exact pathogenesis of DCM and improve the diagnosis and treatment of this disease. The nuclear receptors (NR) superfamily comprises a group of transcription factors, such as liver X receptor (LXR), retinoid X receptors (RXR), retinoic acidrelated orphan receptor-α (RORα), retinoid receptors, vitamin D receptor (VDR), mineralocorticoid receptor (MR), estrogen-related receptor (ERR), peroxisome proliferator activated receptor (PPAR), nuclear receptor subfamily 4 group A 1(NR4A1), etc. Various studies have reported that NRs play a crucial role in cardiovascular diseases. A recently conducted work highlighted function of the NR superfamily in realm of metabolic diseases and their associated complications. This review summarized the available information on several important NRs in the pathophysiology of DCM and discussed future perspectives on the application of NRs as targets for DCM treatment.